2020
DOI: 10.52643/jukmas.v4i2.1026
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penggunaan Alat Kontrasepsi Sebelum Dan Saat Pandemi Covid-19

Abstract: WHO menyatakan penyakit virus korona (COVID-19) sebagai darurat kesehatan global. Pemerintah Indonesia telah menetapkan bencana non alam penyebaran COVID-19 sebagai Bencana Nasional. Dalam menghadapi wabah bencana non alam COVID-19 ini dilakukan kebijakan Pembatasan Sosial Berskala Besar (PSBB) untuk pencegahan penularan COVID-19. Kondisi ini menyebabkan dampak terhadap kelangsungan pelayanan kesehatan masyarakat, termasuk pelayanan KB dan kesehatan reproduksi. Penelitian ini menggunakan teknik kuantitatif den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The COVID-19 pandemic reduced access to public health services, including family planning, because the resources were allocated to deal with the pandemic. 16 The results showed that during the COVID-19 pandemic, there were restrictions on post-partum family planning program services at public health centres, especially long-term contraception services. “ During the COVID-19 pandemic, the long-term contraceptive method was limited to just five a day.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The COVID-19 pandemic reduced access to public health services, including family planning, because the resources were allocated to deal with the pandemic. 16 The results showed that during the COVID-19 pandemic, there were restrictions on post-partum family planning program services at public health centres, especially long-term contraception services. “ During the COVID-19 pandemic, the long-term contraceptive method was limited to just five a day.…”
Section: Discussionmentioning
confidence: 98%
“…However, counselling and services still need to be carried out based on the latest guidelines in the COVID-19 pandemic. 16 The provision of communication, information, and education (CIE) materials and counselling related to reproductive health and family planning can be carried out online or by telephone consultation. 18…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, medical staffs involved in reproductive health care were diverted to accommodate other requirements. For couples of childbearing age who require contraceptive use services and products, such conditions pose serious problems to their health and wellbeing (Aprillia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Indonesia pada tahun 2020 menduduki peringkat pertama di asia tenggara sebagai negara dengan konfirmasi paparan positif Covid-19 terbanyak. 3 Untuk menekan angka pisitif Covid-19 pemerintah Indonesia terus berupaya dengan memberlakukan pembatasan sosial bersekala besar maupun sedang diberbagai wilayah di Indonesia. 4 Upaya lain selain PSBB program ayo vaksin menjadi upaya lain pemerintah untuk mencegah penyebaran Covid-19.…”
Section: Aunclassified